The Role of Paid, Earned, and Owned Media in Building Entertainment Brands: Reminding, Informing, and Enhancing Enjoyment - Lovett, Mitchell J.; Staelin, Richard (Marketing Science, 2016)
We study three ways firms can communicate about their brands—paid media (advertising), earned media (word of mouth and online social media), and owned media (brand websites and other owned content)—and the roles these media types play in reminding (i.e., activating memory), informing (i.e., learning their tastes for the brand), or enhancing enjoyment (e.g., gaining additional utility from socializing about the brand). We do this for a new TV show setting using a data set that contains reported viewing, exposures, expectations, and experiences. We present descriptive analyses and results from a new structural model, which indicate that earned media is more impactful than paid and owned media per exposure. However, paid media has far more exposures, so for a given percentage increase, paid media’s influence dominates earned and owned media. Earned media operate primarily through enhancing enjoyment, whereas paid media operate through reminding and owned media through reminding, but discourage live viewing. We find that media exposures help consumers learn about how well they will like the program. However, this learning can either increase or decrease the expected liking, and in our data the average audience effects are negligible. Overall, we find that earned and paid media play a central role in developing and maintaining entertainment brands.